Dakwah dalam Pendekatan Konsep Ekologi - Vina Fitriani; Mukhlis Aliyudin (Department of Islamic Communication and Broadcasting, Faculty of Dakwah and Communication, UIN Sunan Gunung Djati Bandung, 2021)
ABSTRACT The purpose of this research is to find out what is the background of ecological preaching messages, ecological da'wah activities and to determine the meaning of ecological preaching. The research method used is descriptive qualitative with a phenomenological theory approach. The results obtained explain that the background of ath-thaariq's ecological preaching message, first is the existence of agrarian conflict, second is the green revolution, third is the lack of knowledge and understanding of the community about the environment. Ecological da'wah activities carried out through the concept of planting, maintaining and utilizing the environment. The meaning of ecological da'wah can be viewed in terms of the underlying motive and basic goals expected of the Ath-Thaariq Islamic boarding school in carrying out its da'wah activities through an ecological approach. Da'wah in this ecological approach is very accepted, both by Ath-Thaariq students and the surrounding community. Keywords: Da'wah; Ecology; Islamic Boarding School; ABSTRAK Tujuan penelitian ini untuk mengetahui apa yang melatarbelakangi pesan dakwah ekologis, aktivitas dakwah ekologis serta untuk mengetahui makna dakwah ekologis. Metode penelitian yang digunakan yaitu deskriptif kualitatif dengan pendekatan teori fenomenologi. Hasil penelitian yang diperoleh menjelaskan bahwa yang melatarbelakangi pesan dakwah ekologis ath-thaariq, pertama adanya konflik agraria, kedua adanya revolusi hijau, ketiga kurangnya pengetahuan dan pemahaman masyarakat mengenai lingkungan. Aktivitas dakwah ekologis yang dilakukan melalui konsep penanaman, pemeliharaan serta pemanfaatan lingkungan. Makna dakwah ekologis dapat ditinjau dari segi motive yang mendasari dan dasar tujuan yang diharapkan pesantren Ath-Thaariq dalam melakukan aktivitas dakwahnya melalui pendekatan ekologi. Dakwah dalam pendektan ekologi ini sangat diterima, baik itu oleh santri Ath-Thaariq maupun masyarakat sekitar. Kata Kunci : Dakwah; Ekologi; Pesantren;